Supramolecular imaging of spermine in cancer cells - Tian, Han-Wen; Chang, Yu-Xuan; Hu, Xin-Yue; Shah, Muhammad Raza; Li, Hua-Bin; Guo, Dong-Sheng (Nanoscale, 2021)
As an important biomarker, the overexpressed spermine has been widely investigated for cancer diagnosis and treatment. However, bioimaging of spermine in living cells is still a formidable challenge. Herein, we design a supramolecular imaging ensemble for spermine by the host-guest complexation of amphiphilic sulfonatocalix[5]arene (SC5A12C) assembly with lucigenin (LCG). Strong binding ability and complexation-induced fluorescence quenching properties enable SC5A12C to quench the fluorescence of LCG dramatically and to recover it completely due to the competition of overexpressed spermine in cancer cells. SC5A12C also exhibits excellent biocompatibility and promotes cellular uptake due to its ability to form ultra-stable assembly. Co-assembling folate further promotes the cellular uptake of folate receptor overexpressed cancer cells, contributing to enhanced bioimaging. A supramolecular imaging ensemble for spermine is developed by the complexation of amphiphilic sulfonatocalix[5]arene (SC5A12C) assembly with lucigenin.